Critical curves for a fast diffusive p-Laplacian equation with nonlocal source. Issue 9 (13th June 2022) - Zheng, Yadong; Fang, Zhong Bo
ABSTRACT: This paper deals with the critical curves for a fast diffusive p-Laplacian equation with nonlocal inner source under nonlinear boundary flux in half-line. We obtain new critical global existence curve and critical Fujita curve by constructing various self-similar super- and sub-solutions.